Development and performance of anode material based on A-site deficient Sr2-xFe1.4Ni0.1Mo0.5O6-δ perovskites for solid oxide fuel cells. (10th October 2016) - Feng, Jie; Qiao, Jinshuo; Wang, Wenyi; Wang, Zhenhua; Sun, Wang; Sun, Kening
Abstract: Engineering of A-site deficiency in perovskites can be critical for designing new materials with required functional properties. In this article, A-site deficient Sr2-x Fe1.4 Ni0.1 Mo0.5 O6-δ (x = 0-0.1, Sr2-x FNM) perovskites have been synthesized and characterized as anode materials for solid oxide fuel cells. X-ray photoelectron spectroscopy data indicate that Sr deficiency changes valence states of B-site cations. The introduction of A-site deficiency has shown to improve the chemical stability of the as-prepared materials under reducing conditions. With increasing of Sr deficiency, the conductivity in 5% H2 /Ar increases markedly, reaching a peak value of 26.6 S cm −1 at x = 0.05. While further increasing of x reduces the conductivity by affecting the mobility of electronic charge carriers. The La0.9 Sr0.1 Ga0.8 Mg0.2 O3 electrolyte-supported cell with La0.6 Sr0.4 Fe0.8 Co0.2 O3 cathode and Sr1.95 Fe1.4 Ni0.1 Mo0.5 O6-δ anode demonstrates a maximum power density of 606 mW cm −2 at 800 °C operating in H2 . Such designed A-site deficiency perovskite has the potential to be applied as SOFC anode materials.